Mechanical Characteristics and Energy Evolution Laws for Red Bed Rock of Badong Formation under Different Stress Paths. (2nd May 2019) - Wen, Tao; Tang, Huiming; Wang, Yankun; Ma, Junwei; Fan, Zhiqiang
Abstract : Exploring mechanical properties of red bed rock of Badong Formation Section two (b2) from the Three Gorges Reservoir is crucial to determine the instability mode of reservoir slopes. In order to reveal the energy evolution laws for b2 rocks under different stress paths, loading tests, unloading tests, and cyclic loading-unloading tests were conducted, respectively. The results show that stress paths have significant influences on the mechanical properties and energy evolution characteristics of b2 rocks and the failure mechanism under three stress paths is revealed. Relative to the loading tests, the mechanical parameters of b2 rocks are deteriorated under the unloading conditions. In addition, the increasing trend of cumulative dissipation energy (CDE) is similar with that of total absorption energy (TAE) and the ESE-strain curves are characterized by multistep rise. For cyclic loading-unloading tests, the areas of hysteretic loop gradually increase as the cycle times increase, and the TAEs and the coefficient of the cumulative dissipation energy (CCDE) also increase gradually with approximately linear characteristics, while the CDEs gradually increase in an abrupt rate. This work can contribute to provide the failure mechanism of b2 rocks for evaluating the stability of reservoir slopes from the energy perspective.